Prevalence and risk factors of brucella melitensis in goats and humans and its economic and public health impact in Malaysia - Bamaiyi, Pwaveno Huladeino (2013)
A study was conducted to describe the occurrence and distribution of zoonotic Brucella melitensis in goats in Peninsular Malaysia; estimate the seroprevalence of B. melitensis infection in some farmers, veterinary technical staff and other personnel in three states of Malaysia; identify some risk-factors associated with B. melitensis in humans in Peninsular Malaysia and do a case control study of brucellosis in goat farms in four states; estimate the economic impact of brucellosis in farms in Peninsular Malaysia and isolate B. melitensis and molecularly characterize the isolates. Using serosurveillance data of the last decade (2000-2009) involving 119,799 goats and 3555 farms, the seroprevalence of brucellosis among goats was generally low (0.91%) and general farms seroprevalence was 7.09%. The odds of brucellosis increased significantly (P<0.05) in the later part of the decade, with increase in herd size and in the western region of Malaysia. The seroprevalence rate of brucellosis among 446 farmers and non-farmers (veterinary technical staff and others) was 1.35%. Occupation, age and drinking unpasteurized milk though not statistically significant but were considered risk factors for brucellosis based on their OR values using multivariate logistic regression at 95% confidence level. The odds of having brucellosis increased by 7.19 times in farmers compared to non-farmers (95% CI=0.82, 63.45), it increased 7.16 times in individuals 40 years and below compared with those above 40years old (95% CI=0.82, 62.97) and 4.45 times among those who drink unpasteurized milk compared to those who do not (95% CI= 0.78, 25.33). In the case control study of 42 goat farms: introduction of new animals (OR=5.25; 90% CI=1.46, 18.88); older category of farms (OR=5.53; 90% CI=1.09, 21.66) and having only single breeds of goats on the farm (OR=8.50; 90% CI=1.27, 41.97) were significant risk factors for brucellosis on the farm using multivariate logistic regression at 90% confidence level. Comparing fifteen farms when they had no brucellosis infection and after they were infected with brucellosis using the culling of the goats and farm value as criteria the fifteen farms had a financial loss of at least RM 156,212.50 (USD 50,391.13) which was found to be significant (P<0.05) at 95% confidence level. Brucella melitensis was isolated from 7 (5.22%) out of 134 goats in 4 states in Malaysia with vaginal swabs giving the highest isolation rate (57.14%). The isolates were phylogenetically related to other isolates from India, Iran, Israel but most closely related to isolates reported from Singapore. This indicates a wide geographical distribution of the genotypes. This study highlights the current status of brucellosis in Malaysia and the need for more proactive measures to control and eradicate the infection from the animal and human populations. It shows that goats and humans are infected with brucellosis and certain risk factors encourage the persistence of the infection. Great losses are suffered by farmers due to brucellosis infection on their farms. There is a need to study further other aspects of the epidemiology of brucellosis in Malaysia especially the role of wild life and importation of goats.